PENGARUH KOMUNIKASI TERAPEUTIK TERHADAP PENURUNAN RASA TAKUT PADA ANAK SAAT PENCABUTAN GIGI DI PUSKESMAS PANTAI CERMIN KABUPATEN LANGKAT - Srinur Nilawati (Universitas Pahlawan Tuanku Tambusai, 2022)
One of the most feared dental treatments for children is tooth extraction. Not only children, maybe even adults pay less attention to the condition of dental health. To overcome fear in children, before tooth extraction is carried out, it is necessary to prepare the child mentally. The emergence of fear in children is the result of a child’s mindset regarding dental care through the experience of hearing stories, so that fear is often the cause of children refusing to have treatment. The purpose of this research is to find out how effective therapeutic communication is on fear in children who will have tooth extractions. The high percentage of fear in children when carrying out tooth extraction at the Pantai Cermin Heatlth Center Tanjung Pura in 2022 of 41,7% is a problem in this study. This study used a sampling method using accidental sampling, which is a non random sampling technique with respondents who came to perform tooth extraction in children aged 6-12 years from September 2022 to November 2022 totaling 48 children and dental health workers. The data collection instrument uses a check list sheet and questionnaire sheet. The data analysis technique uses the chi-square test. The result of the study showed that there was an effect of therapeutic communication from health workers on the fear children who will carry out treatment for tooth extraction at Pantai Cermin Health Center Tanjung Pura. Keywords: Therapeutic communication, fear, tooth extraction